TEMPORAL VARIATION IN PETROGRAPHIC FEATURES OF THE MIOCENE JATILUHUR FORMATION IN THE BOGOR TROUGH, WEST JAVA - -, Abdurrokhim; -, Hendarmawan (Bulletin of Scientific Contribution, 2014)
This paper reports on petrographic features Jatiluhur Formation in the northern part of Bogor Trough. On basis of mineral composition from petrographic analysis of sandstone samples, the petrographic features of the Jatiluhur Formation can be classified into 4 petrographic facies as follow: (F1) Feldspathic arenite, (F2) Feldspathic greywacke, (F3) Limestone, and (F4) Mixed siliciclastic and carbonate. The sediments of the Jatiluhur Formation indicate that they were derived mainly from a continental source, including the Sundaland in the north, which is considered to have been the most possible source area for the Paleogene sediments. The increase in relative abundance of volcanic fragments was documented in the late Miocene samples and this suggests that the late Miocene deposits of the Jatiluhur Formation seem to have also received some sediment directly or indirectly from the contemporaneous volcanic provenances to the south.